Paths of Duty American Missionary Wives in Nineteenth-Century Hawaii - Grimshaw, Patricia (University of Hawai'i Press, 2018)
Twenty-three-year-old Laura Fish Judd left rural Massachusetts in 1827 for the Hawaiian islands, one of eighty young American women who enlisted in the effort to Christianize the islands between 1819 and 1850. Only a month before, after receiving a marriage proposal from a young physician in need of a wife to qualify for mission service, she had written in her diary: "'The die is cast.' I have in the strength of the Lord, consented Rebecca-like--I WILL GO, yes, I will leave friends, native land, everything for Jesus." Laura Judd and other ambitious young women consented to hasty marriages with virtual strangers to achieve their goal of carrying Christ's message to the heathen. As Patricia Grimshaw's compelling study makes clear, these women were driven by a desire for important, independent life-work that went well beyond their expected roles as dutiful wives.The ambitions, hopes, and fears of those eighty pioneer women make a poignant and fascinating story. But Paths of Duty does more than recount the experiences of a group of individuals. Grimshaw shows how the mission women reflected the larger society of which they were part, and through their story shed new light on the role of American Protestant mission in Hawaii. Although the women's public role in mission work was limited, they were highly influential in their daily and seemingly mundane interactions with Hawaiian women. The American women's ethnocentricity made them quite incapable of appreciating Hawaiian culture on its own terms, but their notions of proper femininity and female behavior were effectively transmitted to Hawaiian girls and women. Paths of Duty provides a deeper understanding of this neglected process of acculturation in the islands and its eventual implications for Hawaii's entry into the American sphere of influence.